Biological Control of Factor VII - Nemerson, Yale (Thrombosis and Haemostasis, 1976)
The tissue factor pathway is initiated by factor VII in the presence of tissue factor. The first proteolytic reaction involves cleavage of factor X by factor VII. Activated factor X, the product of this reaction, can activate factor VII by cleavage of a specific bond. The apparent coagulant activity of factor VII then rises about 60-fold. Activated factor X can also inactivate factor VII by catalyzing the cleavage of a second bond which results in a three chain molecule. Fragments of Hageman factor and perhaps kallikrein can also activate factor VII. Hageman factor, however, does not catalyze the inactivating cleavage of factor VII at a significant rate.Recent data showing that the tissue factor pathway can activate the intrinsic system are discussed. We have shown that activated factor X, which can be generated by the tissue factor pathway, can feed back and activate factor IX in a calcium and phospholipid requiring reaction.